PENERAPAN PRINSIP-PRINSIP GOOD GOVERNANCE OLEH EKSKLUSIFITAS AKTOR DI MAKASSAR - Ummu Habibah Gaffar (AS-SIYASAH: Jurnal Ilmu Sosial Dan Ilmu Politik, 2021)
This research will further explore the practice of Good Financial Goverance (GFD), with case studies on the partnership process that took place between the city government of Makassar with PT.GMTD in managing the finances for the participation of local government capital. The research will focus on actor relationships taking place between actors involved in capital partnerships as a recipe offered by Good Financial Governance. The research used qualitative method with researcher location in Makassar South Sulawesi, Indonesia.The main argument of this study is to question the claims of Good Financial Governance, which relies on economic development issues and good financial governance by opening investment shells and the involvement of actors outside the government. For this study, the claim is completely wrong. The results of this study found that good financial governance actually gave birth to a new problem that is Exclusivity Actors. Exclusivity of actors as a consequence of the unequal amount of capital on actors involved in Good Financial Governance. Exclusion of Actors Governance impact on the limits of power between governance actors to be biased, depending on the composition of capital in partnership.Keyword : Exclusivity of Actor, Good Financial Governance, Capital Governance